A Chimeric Affinity Tag for Efficient Expression and Chromatographic Purification of Heterologous Proteins from Plants - Sainsbury, Frank; Jutras, Philippe V.; Vorster, Juan; Goulet, Marie-Claire; Michaud, Dominique (Frontiers in Plant Science, 2016)
The use of plants as expression hosts for recombinant proteins is an increasingly attractive option for the production of complex and challenging biopharmaceuticals. Tools are needed at present to marry recent developments in high-yielding gene vectors for heterologous expression with routine protein purification techniques. In this study we designed the Cysta-tag, a new purification tag for immobilized metal affinity chromatography (IMAC) of plant-made proteins based on the protein-stabilizing fusion partner SlCYS8. We show that the Cysta-tag may be used to rapidly purify proteins under native conditions, and then be removed enzymatically to isolate the protein of interest. We also show that commonly used protease recognition sites for linking purification tags are differentially stable in leaves of the commonly used expression host Nicotiana benthamiana, with those linkers susceptible to cysteine proteases being less stable then serine protease-cleavable linkers. As an example we describe a Cysta-tag experimental scheme for the one-step purification of a clinically useful protein, human α1-antitrypsin, transiently expressed in N. benthamiana. With potential applicability to the variety of chromatography formats commercially available for IMAC-based protein purification, the Cysta-tag provides a convenient means for the efficient and cost-effective purification of recombinant proteins from plant tissues.